Aerosol Transmission of the Pandemic SARS-CoV-2 and Influenza A Virus Was Blocked by Negative Ions - Zhang, Cheng; Cui, Huan; Zhang, Chunmao; Chen, Zhaoliang; Jiang, Xinyun; Liu, Jun; Wan, Zhonghai; Li, Jiping; Liu, Juxiang; Gao, Yuwei; Jin, Ningyi; Guo, Zhendong (Frontiers in Cellular and Infection Microbiology, 2022)
The pandemic of respiratory diseases, such as COVID-19 and influenza, has imposed significant public health and economic burdens on the world. Wearing masks is an effective way to cut off the spread of the respiratory virus. However, due to cultural differences and uncomfortable wearing experiences, not everyone is willing to wear masks, there is an urgent need to find alternatives to masks. In this study, we tested the disinfection effect of a portable ionizer on pandemic SARS-CoV-2 (strain V34) and influenza A virus (strain CA04). Negative ions significantly reduced the concentration of particulate matter in the air above, and effectively disinfected viruses sticked to the solid plate at the level of both nucleic acid and virus titer. The disinfection efficiency was >99.8% after 1 h exposure. Moreover, negative ions effectively disinfected aerosolized viruses, the disinfection efficiency was more than 87.77% after purification for 10 minutes. Furthermore, negative ions had a significant protective effect on susceptible animals exposed to viral aerosols. When the negative ionizer was switched from off to on, the inhalation 50% infective dose (ID50) for golden hamsters challenged with SARS-CoV-2 raised from 9.878 TCID50 (95% confidence interval [CI], 6.727 to 14.013 TCID50) to 43.891 TCID50 (95% CI, 29.31-76.983 TCID50), and the inhalation ID50 for guinea pigs challenged with influenza A virus raised from 6.696 TCID50 (95% CI, 3.251-9.601 TCID50) to 28.284 TCID50 (95% CI, 19.705-40.599 TCID50). In the experiment of transmission between susceptible animals, negative ions 100% inhibited the aerosol transmission of SARS-CoV-2 and influenza A virus. Finally, we tested the safety of negative ion exposure. Balb/c mice exposed to negative ions for 4 weeks showed no abnormalities in body weight, blood routine and lung pathology. Our study demonstrates that air ions can be used as a safe and effective means of blocking respiratory virus transmission and contribute to the pandemic prevention and control.